2013
DOI: 10.2174/1381612811319320005
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-induced Oxidative Stress and its Role in Diabetes Mellitus Related Cardiovascular Diseases

Abstract: Diabetes mellitus is associated to an increased risk of cardiovascular diseases. Hyperglycemia is an important factor in cardiovascular damage, working through different mechanisms such as activation of protein kinase C, polyol and hexosamine pathways, advanced glycation end products production. All of these pathways, in association to hyperglycemia-induced mitochondrial dysfunction and endoplasmic reticulum stress, promote reactive oxygen species (ROS) accumulation that, in turn, promote cellular damage and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
427
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 642 publications
(453 citation statements)
references
References 0 publications
14
427
0
12
Order By: Relevance
“…Hyperglycemia activates protein kinase C (PKC) and Poly-ADP ribose polymerase (PARP) pathways; it also enhances formation of advanced glycation end products (AGEs) and polyol and hexosamine pathways. These pathways are activated or enhanced due to mitochondrial superoxide overproduction (12).…”
mentioning
confidence: 99%
“…Hyperglycemia activates protein kinase C (PKC) and Poly-ADP ribose polymerase (PARP) pathways; it also enhances formation of advanced glycation end products (AGEs) and polyol and hexosamine pathways. These pathways are activated or enhanced due to mitochondrial superoxide overproduction (12).…”
mentioning
confidence: 99%
“…Assessment of coronary risk by gender in each glycemic status group revealed that IFG men have a significantly higher risk than their female counterparts, similar to previous results from Modrego et al [47]; however, it should be noted that coronary risk remained similar between genders among diabetics, demonstrating the role of T2DM as a gender-independent cardiovascular risk factor [48]. Although the presence of IFG has been associated with increased cardiovascular risk through its association with comorbities such as dyslipidemia and hypertension [49], several studies have proposed possible mechanisms which chronic IFG may trigger endothelial dysfunction, or at least, play a role in atherogenesis by increasing production of reactive oxygen species [50], advanced glycation endproducts [51], and inducing low-grade inflammation [52]. Likewise, elements such as physical inactivity, lipid-rich and carbohydraterich diets have been linked with prediabetic states [53], yet few studies explore the relationship of these sociodemographic aspects with cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycemia causes oxidative stress [10], which is also associated with progression of T2DM and several diabetic complications [11]. The accumulation of ROS lead to modifications that cause DNA damage on nuclear and mitochondrial DNA [12].…”
Section: Discussionmentioning
confidence: 99%